Induction of cytopathogenicity in mammalian cell lines challenged with culturable enteric viruses and its enhancement by 5-iododeoxyuridine. - Benton, W H (1982)
Cultures of 17 established cell lines were tested against 105 enteric virus types for capacity to support viral replication as indicated by cytopathogenic effect production. Enhancement of susceptibility by treatment of the cells with 5-iododeoxyuridine was evaluated in parallel with untreated cells. Cytopathogenic effect was produced in two or more cell lines by every virus tested except six strains of group A coxsackie virus. No cell line was found to be susceptible to these six virus types. In general, treatment with 5-iododeoxyuridine provided a more rapid onset of cytopathogenic effect in susceptible cells and in some instances resulted in refractory cells becoming permissive to viral replication. The use of 5-iododeoxyuridine allowed two human embryonic lines (HEL-299 and L-132), in combination, to be susceptible to all but the six group A coxsackie virus strains.